Anaesthesia and Anaesthesiologist: The Perception of Attendees at a Medical College in Rural Haryana - Agrawal, Meenu; Meena Singh; Bansal, Pranav; Jindal, Tushar; Yousuf, Ishrat (Academia Anesthesiologica International, 2020)
Introduction: Anaesthesia as a specialty is reaching its zenith with multiple sub-specialties, but anaesthesiologist remains obscure personnel behind the drapes due to lack of public perception and knowledge pertaining to their role. The aim is to the study was conducted to assess the perception and knowledge of general public about the role of anaesthesia and the anaesthesiologist. Subjects and Methods : A prospective, cross-sectional study, conducted in a 500-bedded, rural medical college over a 3-month period. A total of 172 attendees accompanying their patients for surgical procedures were enrolled and assessed based on preformed, pretested questionnaire in the pre-anaesthetic clinic. The questionnaire contained 30 questions to determine their knowledge and attitude towards anaesthesia and anaesthesia provider. Results: Out of total 172 participants, 43.02% % recognized anaesthesiologist as specially trained doctors. Eighty two (47.67%) of the attendees knew that anesthesia is administered by an anesthesiologist but 71.5% were not aware of their role in providing peri-operative care. The attendees apprised of anesthesiologists role in labour analgesia, chronic pain management, intensive care units and emergency resuscitation was Sixty seven (39%), forty nine (28.49%), forty five (26.7%) and twenty six (15.1%) out of 172 respectively. Majority of the attendees (93.6%) were receptive to know more about anaesthesia. Conclusion: The awareness regarding role of anaesthesiologist in general public is still low and the perception of people about anaesthesia as an evolved specialty is lacking. This calls for corrective measures to be taken by the anaesthesiology fraternity for propagation of anesthesiology skills via social media and other government aided platforms.